Role of the area postrema in the hypophagic effects of oleoylethanolamide. (August 2017) - Romano, Adele; Gallelli, Cristina Anna; Koczwara, Justyna Barbara; Braegger, Fiona E.; Vitalone, Annabella; Falchi, Mario; Micioni Di Bonaventura, Maria Vittoria; Cifani, Carlo; Cassano, Tommaso; Lutz, Thomas A.; Gaetani, Silvana
Graphical abstract: Abstract: The satiety-promoting action of oleoylethanolamide (OEA) has been associated to the indirect activation of selected brain areas, such as the nucleus of the solitary tract (NST) in the brainstem and the tuberomammillary (TMN) and paraventricular (PVN) nuclei in the hypothalamus, where noradrenergic, histaminergic and oxytocinergic neurons play a necessary role. Visceral ascending fibers were hypothesized to mediate such effects. However, our previous findings demonstrated that the hypophagic action of peripherally administered OEA does not require intact vagal afferents and is associated to a strong activation of the area postrema (AP). Therefore, we hypothesized that OEA may exert its central effects through the direct activation of this circumventricular organ. To test this hypothesis, we subjected rats to the surgical ablation of the AP (APX rats) and evaluated the effects of OEA (10 mg kg −1 i.p.) on food intake, Fos expression, hypothalamic oxytocin (OXY) immunoreactivity and on the expression of dopamine beta hydroxylase (DBH) in the brainstem and hypothalamus. We found that the AP lesion completely prevented OEA's behavioral and neurochemical effects in the brainstem and the hypothalamus. Moreover OEA increased DBH expression in AP and NST neurons of SHAM rats while the effect in the NST was absent in APX rats, thus suggesting the possible involvement of noradrenergic AP neurons. These results support the hypothesis of a necessary role of the AP in mediating OEA's central effects that sustain its pro-satiety action.